Unforgotten: Love and the culture of dementia care in India - Brijnath, Bianca (2014)
As life expectancy increases in India, the number of people living with dementia will also rise. Yet little is known about how people in India cope with dementia, how relationships and identities change through illness and loss. In addressing this question, this book offers a rich ethnographic account of how middle-class families in urban India care for their relatives with dementia. From the husband who wakes up at 3 am to feed his wife ice-cream to the daughters who gave up employment for seven years to care for their mother with dementia, this book illuminates the local idioms on dementia and aging, the personal experience of care-giving, the functioning of stigma in daily life, and the social and cultural barriers in accessing support.